Isolation and characterization of dihydrofolate reductase from trimethoprim-susceptible and trimethoprim-resistant Pseudomonas cepacia. - Burns, J L (1989)
Trimethoprim resistance was investigated in cystic fibrosis isolates of Pseudomonas cepacia. Determination of the MIC of trimethoprim for 111 strains revealed at least two populations of resistant organisms, suggesting the presence of more than one mechanism of resistance. Investigation of the antibiotic target, dihydrofolate reductase, was undertaken in both a susceptible strain and a strain with high-level resistance (MIC, greater than 1,000 micrograms/ml). The enzyme was purified by using ammonium sulfate precipitation, gel filtration, and ion-exchange chromatography. Specific activities, molecular weights, isoelectric points, and substrate kinetics were similar for both enzymes. However, the dihydrofolate reductase from the trimethoprim-resistant strain demonstrated decreased susceptibility to inhibition by trimethoprim and increased susceptibility to inhibition by methotrexate, suggesting that these two enzymes are not identical. We conclude that the mechanism of trimethoprim resistance in this strain with high-level resistance is production of a trimethoprim-resistant dihydrofolate reductase.